The Wee Free Men [compact disc, unabridged] - Pratchett, Terry (Harper Children's Audio, 2005)
A young witch-to-be named Tiffany teams up with the Wee Free Men, a clan of six-inch-high blue men, to rescue her baby brother and ward off a sinister invasion from Fairyland.